A role for the human single-stranded DNA binding protein HSSB/RPA in an early stage of nucleotide excision repair. - Coverley, D (1992)
The human single-stranded DNA binding protein (HSSB/RPA) is involved in several processes that maintain the integrity of the genome including DNA replication, homologous recombination, and nucleotide excision repair of damaged DNA. We report studies that analyze the role of HSSB in DNA repair. Specific protein-protein interactions appear to be involved in the repair function of HSSB, since it cannot be replaced by heterologous single-stranded DNA binding proteins. Anti-HSSB antibodies that inhibit the ability of HSSB to stimulate DNA polymerase alpha also inhibit repair synthesis mediated by human cell-free extracts. However, antibodies that neutralize DNA polymerase alpha do not inhibit repair synthesis. Repair is sensitive to aphidicolin, suggesting that DNA polymerase epsilon or delta participates in nucleotide excision repair by cell extracts. HSSB has a role other than generally stimulating synthesis by DNA polymerases, as it does not enhance the residual damage-dependent background synthesis displayed by repair-deficient extracts from xeroderma pigmentosum cells. Significantly, when damaged DNA is incised by the Escherichia coli UvrABC repair enzyme, human cell extracts can carry out repair synthesis even when HSSB has been neutralized with antibodies. This suggests that HSSB functions in an early stage of repair, rather than exclusively in repair synthesis. A model for the role of HSSB in repair is presented.